Upaya Meningkatkan Kemampuan Berbahasa dalam Pengenalan Keaksaraan Menggunakan Media Gambar pada Anak Kelompok B2 TK Negeri Pembina Kecamatan Temanggung - Tantik Rusmiyati (Universitas PGRI Semarang, 2020)
Efforts to Improve Language Skills in Introduction to Literacy Using Image Media in Kindergarten Children Group B2 in State Kindergarten Pembina, Temanggung District, 2017-2018 Academic Year. The basis and background of this research is the number of parents of children who want their children to be able to read and write in kindergarten. While achieving this requires an understanding of literacy as a basis for children's ability to start reading beginning. What happens in B2 class is a lot children have not memorized and understood literacy or the letters of the alphabet although in making various good strokes of ability. And the teacher still uses the old pattern so that the child tends to be passive. To be able to investigate this, the researcher takes class action, can literacy recognition be improved by using media images? students of B2 group TK Negeri Pembina, Temanggung District. This research method uses data collection techniques, interview observation, questionnaires and documentation. Technical analysis of the data used in the study is qualitative analysis. Analysis is carried out on qualitative data obtained from observations made on children and things that appear during the course of research. analysis will be used as a basis for the preparation of action plans at a later stage. The results of this study indicate that learning using picture media can improve children's ability in literacy recognition and even improve children's ability to read a few words. Children's creativity, children's shame, children's attention becomes focused, and the learning atmosphere is more interesting and enjoyable. This can be proven from the initial conditions of the ability to recognize literacy which increased 59% to 85%. Out of 24 children, 18 children were able to succeed according to the assessment criteria, 4 children still needed rocks and 2 children still needed intensive guidance.